The I-frame vs. S-frame: how neoliberalism has led behavioral sciences astray - Andreas, Marike; Jabakhanji, Samira Barbara (Frontiers in Psychology, 2023)
In their recently published paper, Chater and Loewenstein critically elaborate on the differences between interventions that focus on individual behavior (‘i-frame’), as opposed to the systems in which health behavior occurs (‘s-frame’). They point out that behavioral scientists frequently rely on individual-level interventions, rather than systemic change to improve population health. As individual-level interventions have fallen short of the author’s expectations to fix health problems, the authors argue that behavioral scientists should focus more on system-level change. They warn behavioral scientists that by framing disease as an individual problem they hinder real change. We agree with the arguments made by the authors; nevertheless, we propose that bringing underlying causes for the i-frame focus to light would advance their argument. In our commentary, we discuss that neoliberalism might be a reason for the focus on individual interventions in behavioral health sciences.